Identification Of Carbohydrate, Protein And Fat Levels In Flour, Cheese, Milk And Yoghurt Through Several Test Methods - Tyasna, Putri Setya; Agustin, Annastya Eka; Maharani, Dhavina; Utami, Marsah Rahmawati; Nurfadhilah, Lina (Sean Institute, 2022)
Food is incoming substance to in body human and processed in a manner chemical and biological like carbohydrates , proteins, and fats. each of third substance this have very important role for body . Carbohydrate useful as one source energy , increase the sweet taste , regulate the process of glucose blood , and can solve fatty acids. Proteins play a role in metabolic processes , catalysts enzymatic , antibody , and carrier signal in a manner biological . Useful fat as warmer body , adjustment with change temperature , and protect body from crash . For knowing how much many content of fat , protein, and carbohydrates contained in a food or drink so need done testing in a manner qualitative and quantitative , testing this depending on the sample being tested and the effect temperature nor ingredient standard used . The purpose of the literature review is to determine and compare the levels of carbohydrates, proteins and fats in samples of flour, milk, cheese and yogurt through various test methods.